PENGARUH PERAN ORANG TUA DAN GURU PENDIDIKAN AGAMA ISLAM TERHADAP KARAKTER SISWA DI ISLAMIC BOARDING SCHOOL BULU SUKOHARJO - Anas Abdullah; Joko Subando (Jurnal Manajemen Pendidikan, 2026)
This study examines the effects of parental roles and Islamic Religious Education teachers on students’ character at SMP El Dzikr Islamic Boarding School Bulu Sukoharjo during the 2025/2026 academic year. It employed a quantitative approach with an ex post facto correlational design. The population comprised 46 students, all of whom were selected as respondents through total sampling. Data were collected using a closed-ended Likert-scale questionnaire measuring parental roles, Islamic Religious Education teachers’ roles, and students’ character. Each variable consisted of ten statement items. Data analysis included validity and reliability tests, normality, linearity, heteroscedasticity, multiple linear regression, partial t-tests, simultaneous F-tests, and the coefficient of determination. The findings showed that parental roles had a positive and significant effect on students’ character, with a regression coefficient of 0.379, a t-value of 2.477, and a significance value of 0.017. The role of Islamic Religious Education teachers also had a positive and significant effect, with a regression coefficient of 0.319, a t-value of 2.517, and a significance value of 0.016. Simultaneously, both variables significantly affected students’ character, as indicated by an F-value of 7.032 and a significance value of 0.002. The two variables explained 24.6% of the variation in students’ character. These findings highlight the importance of consistent role modelling, religious habituation, supervision, communication, and collaboration between families and Islamic boarding schools.